School based sex education and HIV prevention in low- and middle-income countries: a systematic review and meta-analysis. - Virginia A Fonner; Kevin S Armstrong; Caitlin E Kennedy; Kevin R O'Reilly; Michael D Sweat (PLoS ONE)
Objectives School-based sex education is a cornerstone of HIV prevention for adolescents who continue to bear a disproportionally high HIV burden globally. We systematically reviewed and meta-analyzed the existing evidence for school-based sex education interventions in low- and middle-income countries to determine the efficacy of these interventions in changing HIV-related knowledge and risk behaviors. Methods We searched five electronic databases, PubMed, Embase, PsycInfo, CINAHL, and Sociological Abstracts, for eligible articles. We also conducted hand-searching of key journals and secondary reference searching of included articles to identify potential studies. Intervention effects were synthesized through random effects meta-analysis for five outcomes: HIV knowledge, self-efficacy, sexual debut, condom use, and number of sexual partners. Results Of 6191 unique citations initially identified, 64 studies in 63 articles were included in the review. Nine interventions either focused exclusively on abstinence (abstinence-only) or emphasized abstinence (abstinence-plus), whereas the remaining 55 interventions provided comprehensive sex education. Thirty-three studies were able to be meta-analyzed across five HIV-related outcomes. Results from meta-analysis demonstrate that school-based sex education is an effective strategy for reducing HIV-related risk. Students who received school-based sex education interventions had significantly greater HIV knowledge (Hedges g = 0.63, 95% Confidence Interval (CI): 0.49-0.78, p<0.001), self-efficacy related to refusing sex or condom use (Hedges g = 0.25, 95% CI: 0.14-0.36, p<0.001), condom use (OR = 1.34, 95% CI: 1.18-1.52, p<0.001), fewer sexual partners (OR = 0.75, 95% CI:0.67-0.84, p<0.001) and less initiation of first sex during follow-up (OR = 0.66, 95% CI: 0.54-0.83, p<0.001). Conclusions The paucity of abstinence-only or abstinence-plus interventions identified during the review made comparisons between the predominant comprehensive and less common abstinence-focused programs difficult. Comprehensive school-based sex education interventions adapted from effective programs and those involving a range of school-based and community-based components had the largest impact on changing HIV-related behaviors.